Crisi economica e comportamenti illegali (2018)
"Economic and sociological research has long shown that the widespread presence of criminal organizations in the territory is a factor that contrasts economic and social development. This is just one aspect of the complex relationship that exists between local economic dynamics and the illegal behavior of social actors. The relationship between social norms and legal norms, the quality and quantity of social capital, the bonds of trust between the actors and the legitimization of the state, the local power systems, the certainty of the sanctions, are other aspects that certainly contribute to create the conditions that favor illegal responses to the crisis. The book seeks to highlight how legality and illegality present facets and interdependencies that can't simply be traced back to the moral categories of good and evil, but need to be analyzed in a multifactorial perspective."